A2.5 Association study in portuguese patients with ankylosing spondylitis using the immunochip. (31st January 2014) - Pimentel-Santos, F M; Costantino, Félicie; Cortes, Adrian; Garchon, Henri-Jean; Hadler, Johanna; Breban, Maxime; Brown, Matthew A; Branco, Jaime C
Abstract : Background and Objectives: Ankylosing spondylitis (AS), a common inflammatory arthritis affecting primarily the spine and pelvis, is a highly heritable disease. In addition to HLA-B*27, 25 loci were associated with AS in populations of European ancestry in a recent international collaborative study, using the "Immunochip". There is, however, well-known heterogeneity of allele frequencies across populations. We therefore re-examined this large dataset (10, 619 patients and 15, 145 controls) and focused on the Portuguese sample, asking whether alleles might be distinctly associated with AS in Portugal. Materials and Methods: We extracted the data subset corresponding to 184 AS patients (according to the modified New York criteria) and 161 controls, all from mainland Portugal. Written informed consent was obtained from all subjects. Removal of outliers with Eigenstrat and quality control of genotyping data left 325 subjects (174 cases / 151 controls) genotyped with 119768 SNPs. Association analysis was performed using PLINK (v1.07). Results: Apart from the MHC, there was no significant association at the genome-wide level (5 x 10 -8 ). However, 14 SNPs in 12 loci were associated with a nominal P < 1 x 10 -4 . The top-ranking SNP was in the inducible T-cell co-stimulator ligand (ICOSLG) gene (P = 7.56 x 10 -7, OR = 5.014), previously associated in the whole consortium dataset. Other listed loci include USP34, an ubiquitin hydrolase that acts as regulator of the Wnt signalling pathway, CLEC16A, a member of the C-lectin type domain family, and several transcription factors or DNA-binding proteins. Conclusions: Association of ICOSLG points to a potential alteration of the T-cell costimulation pathway in AS pathogenesis and warrants functional studies. Failure to replicate some of the loci associated in the whole consortium dataset likely results from our relatively small sample size. Conversely, new association findings will need confirmation in independent samples and may lead to population-specific genomic variants predisposing to AS.